Effect of regional anesthesia on the postoperative delirium: A systematic review and meta-analysis of randomized controlled trials - Li, Tao; Dong, Tiantian; Cui, Yuanshan; Meng, Xiangrui; Dai, Zhao (Frontiers in Surgery, 2022)
Objective Postoperative delirium (POD) starts in the recovery room and occurs up to 5 days after surgery. While, the POD guidelines issued by the European Society of Anesthesiology (ESA) suggest that the effect of regional anesthesia on pod is controversial. This meta-analysis aims to investigate whether perioperative regional anesthesia reduced the incidence of POD. Methods Standard Published randomized controlled trails (RCTs) were searched from bibliographic databases to identify all evidence reporting regional anesthesia assessing incident delirium following diverse surgeries. The primary outcome was the incidence of POD and the secondary outcomes were POD scores, pain scores and emergence time. The relative risk (RR) for dichotomous outcomes and the weighted or standardized mean difference (WMD, SMD) for continuous outcomes were estimated using a random-effects model. Results 20 RCTs with 2110 randomized participants undergoing different surgeries were included. Meta-analysis showed regional anesthesia was associated with less POD incidence compared to general anesthesia (total intravenous anesthesia (TIVA) or inhalation anesthesia) (relative risk (RR)= 0.62, 95% confidence interval (CI) = 0.45 to 0.85)). Subgroup analysis showed the decrease of POD incidence was associated with nerve block (0.46, 95% CI 0.32 to 0.67) and regional-combined-general anesthesia (0.42, 95% CI 0.29 to 0.60). Regional anesthesia significantly reduced POD incidence in the recovery room after pediatric surgeries (0.41, 95% CI 0.29 to 0.56). Regional anesthesia also reduced POD score (SMD -0.93, 95% CI -1.55 to -0.31) and pain score (SMD -0.95, 95% CI -1.72 to -0.81). There was no significant difference in emergence time between regional anesthesia and general anesthesia (WMD -1.40, 95% CI -3.83 to 6.63). Conclusions There was significant correlation between regional anesthesia and the decreasing of POD incidence, POD score and pain score.